Influence of Different Organic Sources of Nutrient on the Productivity of Upland Rice (Oryza sativa L.) - Mengi, L.; Sarkar, N. C.; Verma, Hemkalyan; Longkumer, L. T. (International Journal of Bio-resource and Stress Management, 2023)
A field experiment was conducted during at the Experimental Research Farm, Department of Agronomy, School of Agriculture Sciences and Rural Development (SASRD), Nagaland University, Medziphema, during kharif season of 2009 to study the influence of different sources of organic nutrients and bio-nutrient on the productivity of upland rice. The experiment was laid out in RBD with seven treatments including control and replicated thrice. The treatments consisted of control, seed inoculation with biofertilizer (Azotobactor) and three sources of organic manures i.e. pig manure, vegetable sea weed manure and vermicompost at the rate of 3.2 t ha-1, 25 kg ha-1 and 2.25 t ha-1 respectively, along with seed treatment with biofungicide (Trichoderma). The experiment results indicated that the application of Biofertilizer+pig manure @ 3.2 t ha-1+Trichoderma significantly increased the growth, yield, yield attributes and nutrient uptake of rice over the other treatments. The maximum plant height (135.37 cm), number of tillers hill-1 (9), dry weight (404.63 g), number of panicle m-2 (122), number of grains panicle-1 (151), grain yield (25.18 q ha-1), straw yield (54.83 q ha-1) were obtained. The maximum uptakes of N (23.86%), P (27.47%) and K (21.83%) in the grain were recorded in the treatment, which was significantly higher over the Biofertilizer+vegetable sea weed manure @ 25 kg ha-1.